EMERGING STRATEGIES FOR ENHANCING EXTERNAL AND INTERNAL P USE EFFICIENCY IN DIFFERENT CROPS/CROPPING SYSTEMS - REDDY, K. SAMMI (The Journal of Research, PJTSAU, 2019)
Phosphorous Use Efficiency of crops is evaluated in terms of apparent recovery, agronomic efficiency and physiological efficiency and is generally low in crops. The agronomic management, fertiliser management , soil management and development of efficient plant root systems, using mycorrhizal association and plant microbial strategies are some of the strategies developed to improve P use efficiency in different crops/ cropping systems. Among the various fertilizer management strategies fertigation is best approach as it not only increases the efficiency but also increases yield and protects environment. P utilization can also be increased by increasing the effective root area and by modifications in rhizosphere. However to increase the P use efficiency inIndia measures should be advocated by the Govt. to encourage use of partially acidulated phosphate rocks which are less costlier than SSP in neutral to alkaline soils with medium P in long term crops and cropping systems. Further focused research on development of CRF’s like polymer blended P, exchanger P, coating of P with nano particles and varieties with high P acquisition efficiency is essential.